Finding Meaning in Suffering: The Role of Spirituality in Existential Psychotherapy for Emotional Recovery in Palliative Care Across Turkey, China, India, Iran, USA, and Denmark - Calderone, Andrea (Journal of religion and health, 2026)
Spiritual support is increasingly recognized as a vital component of psychological care in palliative settings, yet its impact on emotional recovery is not fully established. The objective is to systematically review the benefits of integrating spiritual support into psychotherapy for improving emotional recovery in palliative care. A systematic search of PubMed, Web of Science, and Embase was conducted (September 1-10, 2024) with no date limits. Eligible studies included original research assessing the effects of spiritual support within psychotherapy among palliative care populations. Two independent reviewers performed study selection, data extraction, and risk of bias assessment using ROBINS-I. Discrepancies were resolved by a third reviewer. The review protocol was registered in OSF (https://doi.org/10.17605/OSF.IO/B8SJN). Out of 566 identified articles, 8 met inclusion criteria, encompassing cross-sectional, qualitative, descriptive, and mixed-methods studies from Turkey, China, India, Iran, USA, and Denmark. Integrating spiritual support was consistently associated with improved emotional recovery, including reduced anxiety and depression, enhanced resilience, and greater patient satisfaction. Methodological limitations and moderate/serious risk of bias were noted in several studies. Spiritual support integrated into psychotherapy may significantly improve emotional outcomes in palliative care. Further high-quality research is needed to guide clinical implementation and standardize spiritual care practices.